Implementing TikTok-Based Health Literacy Interventions for Cyberbullying Mitigation among Junior High School Students - Suriah Suriah; Nur Fauziah; Shanti Riskiyani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Cyberbullying is one of the crimes based on the advancement of information technology, often perpetrated through social media with the intention of deliberately and repeatedly hurting someone. Cyberbullying is a problem contributing to the increasing incidence of mental disorders among teenagers today, thus requiring specific intervention. This study aims to assess the utilization of TikTok media in preventing cyberbullying among junior high school students. Method: The study employed a pre-experimental design with the one-group pre-test post-test design. The population consisted of all students of junior high school 21 Makassar totalling 671 individuals, with a sample size of 182 respondents selected using purposive sampling technique. Data were analysed using the Wilcoxon Sign Rank Test. Result: There was an influence of utilizing TikTok media in preventing cyberbullying among junior high school students in Makassar (p = 0.000). Conclusion: The study findings indicate that the use of TikTok media was associated with observable positive behavioral shifts among junior high school students, suggesting its potential utility in health literation initiatives aimed at preventing cyberbullying.